Hybrid Differential Evolution - Particle Swarm Optimization Algorithm for Solving Global Optimization Problems - Pant, M.; Thangaraj, R.; Grosan, C.; Abraham, A. (2008 Third International Conference on Digital Information Management, 2008)
This paper presents a simple, hybrid two phase global optimization algorithm called DE-PSO for solving global optimization problems. DE-PSO consists of alternating phases of differential evolution (DE) and Particle Swarm Optimization (PSO). The algorithm is designed so as to preserve the strengths of both the algorithms. Empirical results show that the proposed DE-PSO is quite competent for solving the considered test functions as well as real life problems.